PERSEPSI PENDERITA TUBERKULOSIS PARU TENTANG KONSUMSI OBAT ANTI TUBERKULOSIS PARU (OAT) DI WILAYAH KERJA PUSKESMAS SIMUNDOL KECAMATAN DOLOK SIGOMPULON KABUPATEN PADANG LAWAS UTARA TAHUN 2015 - Damanik, Dady Hidayah; Pohan, Mahdalena .; Herawati, Lili . (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Pulmonary tuberculosis is a disease caused by mycobacterium tuberculosis, the aerobic bacteria that can live primarily in the lungs or in various other body, resistant to acids and growth of bacteria occurs very slowly, these bacteria are not resistant to ultra violet, because it is transmitted on the evening. This study is a qualitative study aimed to describe Tuberculosis Patient Perceptions of AntiTuberculosis Drug Consumption (OAT) in the sub-district Puskesmas Simundol Dolok Sigompulon North Padang Lawas District in 2015. This study used in-depth interviews as a tool to collect data. Informants in this study as many as six people. The results showed that the overall informant tuberculosis has a good perception about the disease tuberculosis, perception enough about the causes of lung tuberculosis, the perception is quite the transmission of lung tuberculosis, the perception is quite the cure for tuberculosis, the perception is quite the anti-tuberculosis drugs lungs and perception both the old and the type of anti-tuberculosis drugs lungs.